PHILOSOPHY OF THE TRANSCENDENTAL TRUTH (DISTINCTIVE VIEW OF ADVAITA VEDANTA) - Shekhawat, Ishvar Singh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Under the contemplation of the true nature of the Self, differences appear before us. All those differences are resolved by the Upanishads; He comes forward and tries to reconcile all the differences by teaching the path of the Brahma Sutras. In the deep contemplative tradition of Indian philosophy, thoughts are constantly presented on the seeds of thinking about the transcendental principle, which is tried to be known at various places by the name of Brahma. All those ideas are clarified in Advaita Vedanta. There the doubts in everyone's thoughts are clarified that the state of 'Sarvam Khalvidam Brahma' is the real one That is present before all of us after the continuous penance of life. Vedantic sages told this based on their actual experience that man can know this only by experiencing it himself. This cannot be told based on mere thoughts.